The Madhhab-Oriented Paradigm in Fiqh Instruction at Salafiyah-Style Islamic Boarding Schools in Mandailing Natal Regency and Its Relevance to the Reform of Family Law in Indonesia - Muhammad Fadhlan Is; Dede Hafirman Said (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Mandailing Natal Regency is recognized as a